2018
DOI: 10.1155/2018/4092681
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Cognitive Small Cell and WiFi System: A Traffic Balancing Dual‐Access Resource Allocation Scheme

Abstract: We consider a holistic approach for dual-access cognitive small cell (DACS) networks, which uses the LTE air interface in both licensed and unlicensed bands. In the licensed band, we consider a sensing-based power allocation scheme to maximize the sum data rate of DACSs by jointly optimizing the cell selection, the sensing operation, and the power allocation under the interference constraint to macrocell users. Due to intercell interference and the integer nature of the cell selection, the resulting optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Compared with other ML models, execution speed is a major advantage. To quantify uncertain information and dataset, the paper uses entropy as a method to gauge uncertainty and level of chaos in (1). Entropy is a measure of the impurity in a collection of training examples.…”
Section: G O Design Pattern and Dtbfr Mechanismmentioning
confidence: 99%
“…Compared with other ML models, execution speed is a major advantage. To quantify uncertain information and dataset, the paper uses entropy as a method to gauge uncertainty and level of chaos in (1). Entropy is a measure of the impurity in a collection of training examples.…”
Section: G O Design Pattern and Dtbfr Mechanismmentioning
confidence: 99%
“…In [8], authors have studied the impact of SC bandwidth requirements on strategic operators and showed that by imposing a required minimum bandwidth allocation on small cells, the optimal bandwidth allocation strategies of service providers can change dramatically. Authors in [9] studied the existence of both licensed and unlicensed spectrum on SCs. In [10], authors have studied the capacity performances of an SBS by varying the number and the characteristics of operating spectrum bands of an SBS.…”
Section: Introductionmentioning
confidence: 99%